2011
DOI: 10.1111/j.1365-294x.2011.05085.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences in telomere selection in the wild

Abstract: Telomere length is restored primarily through the action of the reverse transcriptase telomerase, which may contribute to a prolonged lifespan in some but not all species and may result in longer telomeres in one sex than the other. To what extent this is an effect of proximate mechanisms (e.g. higher stress in males, higher oestradiol/oestrogen levels in females), or is an evolved adaptation (stronger selection for telomere length in one sex), usually remains unknown. Sand lizard (Lacerta agilis) females have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 56 publications
6
92
1
Order By: Relevance
“…some penguins). Furthermore, sex-specific telomere loss rates have not been found in other monomorphic avian species with equal or female-biased parental care [15,27]. A phylogenetically-controlled inter-species comparison is needed to determine if the care-giving gender is longer-lived than the other and whether this trait is adaptive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…some penguins). Furthermore, sex-specific telomere loss rates have not been found in other monomorphic avian species with equal or female-biased parental care [15,27]. A phylogenetically-controlled inter-species comparison is needed to determine if the care-giving gender is longer-lived than the other and whether this trait is adaptive.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific TL is documented in many taxa [15,16], but often in species with female-biased parental care and large sexual dimorphism in body size. When neonates do not differ in TL, such differences may be related to level of parental investment or developmental rates [3].…”
Section: Introductionmentioning
confidence: 99%
“…lizards [31]. We interpret this finding as reflecting heterogeneity in individual quality, a phenomenon observed in many species [58][59][60], including common terns [34,44,61].…”
Section: Discussionmentioning
confidence: 95%
“…Pauliny et al [16] found a positive relationship between residual telomere length and lifetime reproductive success (number of recruiting progeny) in male dunlins (Calidris alpina) (note, however, that they analysed gels using a computer program now known to be flawed [30]). In sand lizards (Lacerta agilis), female telomere length showed a positive relation with number of hatchlings, but a quadratic relationship with produced recruits in that individuals with intermediate telomere length were least successful [31].…”
Section: Introductionmentioning
confidence: 99%
“…Telomere length appears to have a substantial heritable component in many species [14,41,42]. As a state variable, telomeres may further fill the requirements of positive statebehaviour feedback loops required in state-dependent models of personality behaviour if state variables are not inherently stable [2,4].…”
Section: Discussionmentioning
confidence: 99%